2016
DOI: 10.1128/aac.03003-15
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Protects Escherichia coli from Rapid Antimicrobial-Mediated Killing

Abstract: The contribution of reactive oxygen species (ROS) to antimicrobial lethality was examined by treating Escherichia coli with dimethyl sulfoxide (DMSO), an antioxidant solvent frequently used in antimicrobial studies. DMSO inhibited killing by ampicillin, kanamycin, and two quinolones and had little effect on MICs. DMSO-mediated protection correlated with decreased ROS accumulation and provided evidence for ROS-mediated programmed cell death. These data support the contribution of ROS to antimicrobial lethality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…However, possible interactions between DMSO and antibiotics also need to be addressed. It has recently been reported that DMSO inhibits the action of some reactive oxygen species-dependent antibiotics against Escherichia coli (54). In light of this report, we have tested the effect of DMSO on the efficacy of six different antibiotics against P. aeruginosa.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, possible interactions between DMSO and antibiotics also need to be addressed. It has recently been reported that DMSO inhibits the action of some reactive oxygen species-dependent antibiotics against Escherichia coli (54). In light of this report, we have tested the effect of DMSO on the efficacy of six different antibiotics against P. aeruginosa.…”
Section: Figmentioning
confidence: 99%
“…It has recently been reported that DMSO affects antibiotic susceptibilities in Escherichia coli (54). To test whether DMSO interferes with the effect of conventional antibiotics, we tested the MICs of six antibiotics from different classes for P. aeruginosa in the presence of different concentrations of DMSO.…”
Section: Figmentioning
confidence: 99%
“…On the other hand, DMSO can alter cell membrane permeability, which is speculated to explain its inhibitory effect, and can result in an apparent increase in potency, as the entry into the cell by certain antibiotics is facilitated. Ultimately, these findings discourage the use of DMSO as a solvent for antimicrobials, especially in rapid-killing assays [37].…”
Section: Antibioticmentioning
confidence: 99%
“…The ROS-driven potentiation of killing by both antibiotic treatment and TLD can be abrogated through the addition of ROS mitigators to the culture medium (1,5,12). For example, dimethyl sulfoxide (DMSO) and 2,2’-bipyridine (BiP), both, effectively mitigate the accumulation of antibiotic-induced ROS (5, 17). Using microscopy to quantify ssDNA gaps and DSBs in cells undergoing TLD, Hong and co-workers discovered that thymine starvation initially leads to the accumulation of ssDNA gaps, which are subsequently converted to DSBs in an ROS-dependent process (5).…”
Section: Mainmentioning
confidence: 99%